Knowledge mapping of metformin use on cancers: a bibliometric analysis (2013–2023) - Pan, Chaomin; Wei, Yiyi; Dai, Jingping; Yang, Li; Ding, Zhuoyu; Xinke Wang, (Frontiers in Pharmacology, 2024)
There is substantial evidence from clinical and preclinical studies suggesting an association between metformin use and a reduced risk of cancer. However, the effects of metformin use on cancershave not yet been subjected to bibliometric analysis. The goal of this study was to explore the potential effects of metformin use on cancers and to conduct a comprehensive assessment of research hotspots related to the use of metformin on cancers. The results of the literature analysis were visualized using various tools such as Adobe Illustrator CC 2018, VOSviewer, CiteSpace, and the R package "bibliometrix." The average annual publications from 2013 to 2023 was 372. In terms of journals and co-cited journals, a total of 1064 journals published 1958 papers, and Oncotarget published the highest number of papers (n = 153, 7.81%), while Cancer Research (Co-citation = 5125) was the most frequently cited journal. A total of 25,665 authors participated in the research on metformin use on cancers. Metformin has demonstrated improved outcomes in various types of cancer, including breast cancer (BC), lung cancer (LC), colorectal cancer (CRC), prostate cancer (PC), and pancreatic cancer. This bibliometric analysis reviews the current literature on the clinical data on metformin use on cancers and describes the preclinical evidence illustrating the potential mechanisms of metformin use on various cancers directly or indirectly.